Effect of hemicellulose liquid phase on the enzymatic hydrolysis of autohydrolyzed Eucalyptus globulus wood - Romaní, Aloia (2014)
In this work, Eucalyptus globulus wood was pretreated under non-isothermal autohydrolysis process at 210, 220, and 230 °C, obtaining a pretreated solid with high cellulose content and a hemicellulosic liquid phase (HLP) containing mainly xylose, acetic acid, furfural, xylooligosaccharides, and phenolic compounds. The maximum concentration of xylooligosaccharides (8.97 g/L) and phenolic compounds (2.66 g/L) was obtained at 210 and 230 °C, respectively. To evaluate the effect of HLP addition on the enzymatic hydrolysis using unwashed pretreated solid as substrate, different proportions of HLP were studied. Also, in order to use the whole slurry on enzymatic hydrolysis, the supplementation of xylanases was evaluated. Glucose concentration of 107.49 g/L (corresponding to 74.65 % of conversion) was obtained using pretreated solid at 220 °C liquid/solid ratio (LSR) of 4 g/g and enzyme solid ratio (ESR) of 25 FPU/gwithout the addition of HLP. Thus, it was shown that the unwashed pretreated solids are susceptible to enzymatic hydrolysis contributing to reduce operational cost (water consumption). Additionally, the influence of the inhibitory compounds in the HLP was shown to affect the enzymatic hydrolysis. Results indicated that 82.52 g/L of glucose (59.37 % of conversion) was obtained, using 100 % of HLP at LSR of 4 g/g and ESR of 16 FPU/g at 210 °C of pretreated solid. However, a positive effect was shown on the enzymatic hydrolysis when the xylanases were added using 100 % of HLP, increasing to 35 and 27 % in the glucose production with respect to whole slurry without addition of xylanases.